Human spindle-shaped urine-derived stem cell exosomes alleviate severe fatty liver ischemia–reperfusion injury by inhibiting ferroptosis via GPX4 - Shangheng Shi; Cunle Zhu; Shangxuan Shi; Xinqiang Li; Imran Muhammad; Qingguo Xu; Xinwei Li; Ziyin Zhao; Huan Liu; Guangming Fu; Meiying Song; Xijian Huang; et al. (Stem Cell Research & Therapy)
Abstract Background Severe hepatic steatosis can exacerbate Ischemia–reperfusion injury (IRI), potentially leading to early graft dysfunction and primary non-function. In this study, we investigated the heterogeneity of different subpopulations of Urine-derived stem cells (USCs) to explore the most suitable cell subtype for treating severe steatotic liver IRI. Methods This study utilized scRNA-seq and Bulk RNA-seq to investigate the transcriptional heterogeneity between Spindle-shaped USCs (SS-USCs) and Rice-shaped USCs (RS-USCs). Additionally, rat fatty Liver transplantation (LT) model, mouse fatty liver IRI model, and Steatotic Hepatocyte Hypoxia-Reoxygenation (SHP-HR) model were constructed. Extracellular vesicles derived from SS-USCs and RS-USCs were isolated and subjected to mass spectrometry analysis. The therapeutic effects of Spindle-shaped USCs Exosomes (SS-USCs-Exo) and Rice-shaped USCs Exosomes (RS-USCs-Exo) were explored, elucidating their potential mechanisms in inhibiting ferroptosis and alleviating IRI. Results Multiple omics analyses confirmed that SS-USCs possess strong tissue repair and antioxidant capabilities, while RS-USCs have the potential to differentiate towards specific directions such as the kidney, nervous system, and skeletal system, particularly showing great application potential in renal system reconstruction. Further experiments demonstrated in vivo and in vitro models confirming that SS-USCs and SS-USCs-Exo significantly inhibit ferroptosis and alleviate severe fatty liver IRI, whereas the effects of RS-USCs/RS-USCs-Exo are less pronounced. Analysis comparing the proteomic differences between SS-USCs-Exo and RS-USCs-Exo revealed that SS-USCs-Exo primarily inhibit ferroptosis and improve cellular viability by secreting exosomes containing Glutathione Peroxidase 4 (GPX4) protein. This highlights the most suitable cell subtype for treating severe fatty liver IRI. Conclusions SS-USCs possess strong tissue repair and antioxidant capabilities, primarily alleviating ferroptosis in the donor liver of fatty liver through the presence of GPX4 protein in their exosomes. This highlights SS-USCs as the most appropriate cell subtype for treating severe fatty liver IRI.